The md-Matrix: A learning tool in the mobile application development course - Shiratuddin, Norshuhada; Sarif, Siti Mahfuzah (Inderscience, 2009)
An electronic decision matrix-based on the Pugh method, called the md-Matrix, to be used as one of the learning tools in a mobile development course, is introduced. The md-Matrix is designed and developed to assist developers (especially the novice) to choose the methodology that suits the requirements of their mobile development projects based on Software Development Methodology (SDM) properties. Detailed descriptions of how the md-Matrix can be used in facilitating the learning process of mobile development are elaborated in this paper. The results from the users' perceived usefulness evaluation are also discussed in this paper.